Quantifying Stock Trading Volume in the Transportation Sector in View of Global Geopolitical Risk (GPR), World Oil Prices, and Inflation - Syarief Hidayat; Euis Mufahamah; Anita (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the influence of global geopolitical tensions (Geopolitical Risk/GPR), world oil prices, and inflation on the trading volume of transportation sector stocks in Indonesia. The transportation sector was chosen because it is highly sensitive to changing global conditions, energy costs, and domestic macroeconomic pressures. This study uses a quantitative approach with monthly secondary data for the period January 2022-December 2024 on five transportation sector companies listed on the Indonesia Stock Exchange, namely SMDR, ASSA, TAXI, BLTA, and TMAS. The analysis method used was panel data regression with model selection through Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that GPR, world oil prices, and inflation simultaneously have a significant effect on the trading volume of transportation sector stocks. Partially, GPR affects trading activities due to increasing market uncertainty, world oil prices affect trading volumes through changes in company operating costs, and inflation affects investor behavior related to risk expectations and purchasing power. These findings indicate that external dynamics and macroeconomic conditions play an important role in determining the liquidity and trading activities of the transportation sector in Indonesia.